Gel formation mechanism and gel properties controlled by Ca2+ in chia seed mucilage and model substances - Brax, Mathilde; Schaumann, Gabriele Ellen; Diehl, Dörte (Journal of plant nutrition and soil science, 2019)
Polygalacturonic acid (PGA) is considered as a model substance for mucilage to study mucilage–soil interactions, assuming that the gel formation mechanism of mucilage is comparable to the one of PGA. However, some studies question the accepted hypothesis, which states that, like for PGA, this mechanism relies on cross‐links between uronic acid and calcium for mucilage. The aim of this study was therefore to understand the influence of the abundance and degree of esterification of uronic acids and the influence of calcium on the gel formation mechanism in mucilage as compared to model substances. The mucilage used was from chia seeds, as it is easily available in great quantity and has gel properties shared by root mucilage. Results reported here demonstrate that, while the gel formation mechanism of PGA relied on specific cross‐links with calcium and led to heterogeneous gels, low‐methoxy pectin (LMP) formed homogeneous calcium gels also characterized by nonspecific ionic interactions with calcium. On the contrary, despite similar uronic acid content to LMP, chia seed mucilage was mostly governed by weak electrostatic interactions between entangled polymer chains, which conferred the gel poor water retention. Addition of calcium reduced repulsion and molecular expansion, resulting in a reduction of the water content in chia seed mucilage. Finally, the discrepancies between PGA, LMP and chia seed mucilage discredit the use of PGA as model for chia seed mucilage. Comparison with root mucilage is still needed. This study offers the keys for further mechanistic understanding on the influence of mucilage on soil properties.